ROLE OF PLANT GROWTH PROMOTING IN IMPROVING PRODUCTIVITY AND QUALITY OF MAIZE - Al-Temimi, Athir H. M.; Al-Hilfy, Intsar H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate effect of minerals, organic and bio- fertilizers on yield and quality of three synthetics varieties of maize. A field experiments were applied at the research station of the College of Agricultural Engineering Sciences - University of Baghdad during 2019 and at Abu Ghraib research station during 2020, using randomized complete block design (RCBD) within split-plot arrangement with three replicates. The experiments included two factors, the first in the main plots represented three synthetic varieties of maize, while the second in the sub plots represented five fertilizer treatments. The results showed that bhooth 5018 variety was superior in grain yield during second season, and oil at first season, while Baghdad 3 was superior in number of rows ear-1 in the first season produced highest mean 14.98 row ear-1.While the fertilizer treatment (50% mineral fertilizer + 10% algae extract) was superior in both seasons in grain yield (9077, 7745 kg.h-1) respectively, and most of yield components. The treatment of 100% mineral fertilizer was superior in first season in weight of 500 grains (111.78g).